Trends of sphincter-preserving surgeries for low lying rectal cancer: A 20-year experience in China - Zheng, Kuo; Hu, Qingqing; Yu, Guanyu; Zhou, Leqi; Yao, Yuting; Zhou, Yuan; Wang, Hao; Hao, Liqiang; Yu, Enda; Lou, Zheng; Zhang, Yongjing; Qiu, Hong; et al. (Frontiers in Oncology, 2022)
Background Over the last 2 decades, patients with low rectal cancer have had better outcomes from improvements in surgical techniques in sphincter preservation. We aimed to quantify the trends in sphincter-preserving surgeries for low rectal cancer over 20 years in a top tertiary hospital in China. Methods Between 1999 and 2021, a cohort of patients with primary malignant rectal tumor ≤5cm from the anal verge and who received elective surgeries at Changhai Hospital, Shanghai, China, was identified. Data were extracted from electronic medical records. A Joinpoint Regression Model was used to analyze trends in surgical procedures by average annual percentage change (AAPC). Adjusted Cox proportional hazards regression model was used to assess overall survival. Results Among a total of 4,172 patients during the study period, 3,111 (74.6%) underwent a sphincter-preserving surgery and 1,061 (25.4%) received APR. Sphincter-preserving surgery increased 3.6% per year (95%CI, 2.3-4.9). Low anterior resection was the most performed procedure (86.3%) and maintained a steady trend, while intersphincteric resection increased 49.4% annually (95%CI, 19.5-86.7) after initiation. Laparoscopic techniques increased 15.1% per year (95%CI, 8.4-43.4) after initiation. Sphincter-preserving surgery increased annually for tumors ≤2cm, 2-≤3cm and 3-≤4cm from the anal verge (AAPC 7.1, 4.5-9.8; 4.7, 3.1-6.3; 2.7, 1.7-3.6, respectively). Furthermore, patients with sphincter-preserving surgery had a better overall survival than abdominoperineal resection (APR) patients (adjusted HR 0.78, 95% CI, 0.65-0.93, p=.01). Conclusions Utilization of sphincter-preserving surgeries increased significantly over the last 20 years. Patients with low rectal cancer who underwent sphincter preservation had better survival than similar patients who underwent APR.